Identification Of Constraints On The Maneuvers Of The SPOB OPS ALTAIR Vessel When Berthing At Ramba Jetty, Palembang - Pranata, Pramadyka Deffa; Suherman; Hariyanti, Retno (Jurnal Navigsi Maritim, 2025)
Berthing is a crucial stage in ship operations, including loading and unloading and embarking passengers. This study focuses on the incident of a rope entanglement in the propeller of the SPOB OPS ALTAIR vessel while maneuvering at Ramba Jetty. The objective of the study was to analyze the causes of the incident and possible preventative measures. The method used was descriptive qualitative with data collection techniques through field observation, interviews with the ship's crew, and visual documentation. Analysis was conducted using a fishbone diagram to identify the root cause of the problem. The results showed that the incident occurred due to a lack of monitoring of the area around the ship by the crew, strong current conditions, and minimal lighting around the jetty. The impact was the failure of the ship's starboard engine, so that maneuvers were carried out only with one engine and the bow thruster. Handling efforts can be done through the cutting of entangled ropes by divers, enforcement of garbage disposal regulations by port authorities and improved communication between ship crews and port authorities.